The Effectiveness of Online Collaborative Learning on Students Writing Skills - Uci Nur Maulidah; Imam Nur Aziz (STAI Miftahul Ula Nganjuk, 2020)
Online collaborative learning is learning that focuses on group cohesiveness with the success of the process. The inspiration that drives this assessment is to investigate the impact of the use of online collaborative learning on students' ability to write descriptive texts. it's done in MTS. BUSTANUL ULUM in the second class of juniors to find out whether online collaborative learning is effective learning, researchers used pre-experimental methods where information was calculated using the statistical formula of the T-test. the consequence of exploration was that the mean of the pre-test was 60.4063, and the mean of the post-test was 84.4688. From the questionnaire, there were students who agreed with the online collaborative learning method that had helped them in writing descriptive text. It can be concluded that student achievement increases when they are educated by collaborative learning online.